The Level of Educational Services Quality in Saudi Universities according to a Developed Scale University of Imam Muhammad bin Saud Islamic Model - Nouf Abdulaali Al-Ajmi; Fatema Abdulaziz Al-Twaijri (University of Science and Technology, Yemen, 2016)
Abstract: This study aimed to develop an instrument to measure the quality of educational services provided to students. This instrument was extracted from HEDPERF instrument, and standards of the National Commission for Academic Accreditation and Assessment, Saudi Arabia. And testing the ability of the instrument to determine the quality of the educational services(academic, administrative, and facilities and equipment, and the degree of reputation and renown),  provided to students of mathematics and Physics departments, Faculty of Science, Imam Muhammad bin Saud Islamic University as well as the degree of overall satisfaction. Descriptive method was used. The findings of the study is that the overall average score for the approval of the axis of the quality of academic services, and the axis of the quality of administrative services, and the axis of the quality of facilities and equipment, and the axis of the quality reputation and renown in the sections of mathematics and physics at the Faculty of Natural Sciences phrases came largely neutral. Also, degree of satisfaction with the educational services of (58%) the study members was medium, while (17.6%) of the members of the study, the degree of their approval of the quality of educational services provided weak. while(15%), of the study members were dissatisfied with the educational services provided. (5%) expressed a high approval of  the quality of educational services altogether were (4.25%) did not specify  their point of view of quality educational services.